Improved Brain Pathology and Progressive Peripheral Neuropathy in a 15 Year Old Survivor of Infantile Krabbe Disease Treated With Umbilical Cord Transplantation - Kofler, Julia; Beltran-Quintero, Maria L.; Rugari, Anne; Zuccoli, Giulio; Klotz, Sarah; Escolar, Maria L. (Frontiers in Molecular Neuroscience, 2022)
Objective Krabbe disease is a fatal leukodystrophy caused by deficiency in galactocerebrosidase enzyme activity. The only currently available therapy is hematopoietic stem cell transplantation with bone marrow or umbilical cord blood (UCBT), which leads to increased lifespan and functional abilities when performed in the preclinical stage. While stabilization of white matter disease has been seen on serial MRI studies, neuropathological changes following transplantation have not been documented so far. Materials and Methods We report the first postmortem examination of a 15-year-old female patient with infantile Krabbe disease after UCBT in infancy. Results In contrast to an untreated Krabbe disease brain, which showed severe myelin and oligodendrocyte loss with occasional globoid cells, the transplanted brain displayed markedly improved myelin preservation, but not reaching normal myelination levels. Consistent with the transplanted patient’s clinical presentation of pronounced deficits in gross motor skills, corticospinal tracts were most severely affected. No globoid cells or evidence of active demyelination were observed in the central nervous system, indicative of at least partially successful functional restoration. This was corroborated by the identification of male donor-derived cells in the brain by in situ hybridization. Unlike the observed disease stabilization in the central nervous system, the patient experienced progressive peripheral neuropathy. While diminished macrophage infiltration was seen postmortem, peripheral nerves exhibited edema, myelin and axon loss and persistent Schwann cell ultrastructural inclusions. Conclusion Umbilical cord blood transplantation was able to alter the natural disease progression in the central but less so in the peripheral nervous system, possibly due to limited cross-correction of Schwann cells.